Assessment of Morpho-Physiological, Yield and Yield Attributing Traits Related to Post Anthesis Drought in Wheat Genotypes Under Rainfed Condition in Rampur, Chitwan - Ojha, A.; Ojha, B.R. (International Journal of Applied Sciences and Biotechnology, 2020)
A set of twenty wheat (Triticum aestivum L.) genotypes was evaluated to assess morpho-physiological, yield and yield attributing traits related to post-anthesis drought in wheat genotypes under rainfed condition in a Randomized completely block design with three replications at research farm of Faculty of Agriculture, Rampur, Chitwan, during winter season of 2016/2017. The result revealed highly significant genotypic effects for number of tillers per m2 area, plant height, spike length, number of grains per spike, weight of grains per spike, 1000 kernels weight, days to booting, days to heading, days to anthesis, days to flag leaf senescence, days to maturity, SPAD meter reading, peduncle length, grain filling duration and reproductive growth period. Significant genotypic effects were found for grain yield, biological yield and harvest index and an array of variation was found among the genotypes for each trait. But non-significant genotypic effect was found for canopy temperature depression. WK2373 gave highest grain yield kg/ha (3035 kg/ha) and biomass yield kg/ha (8080 kg/ha).This study presented WK2373, WK2379, WK2380, WK2386, WK2388, WK2383, WK 2378 and WK1481 the best genotypes governing different valuable traits. These potential genotypes for valuable traits found in different clusters. Crossing genotypes belonging to different clusters could maximize the opportunities for transgressive segregation as there is a higher probability that unrelated genotypes would contribute unique desirable alleles at different loci.  Therefore, this study can help breeders to increase genetic diversity by selecting materials of divergent parentage for crosses, thereby reducing vulnerability to diseases and climate changes. Int. J. Appl. Sci. Biotechnol. Vol 8(3): 323-335